Waste valuing from urban wood management through design. Ideas from the case of Sãn Paulo - Cyntia Malaguti de Sousa (Agathón)
As cities grow, urban afforestation becomes more important both for aesthetics and environmental reasons. Nevertheless, pruning and removal of fallen trees, demand a waste management system, not easy to deal with, especially in big tropical cities, such as São Paulo, in Brazil. On the other hand, part of this waste could be employed in wooden artefacts production, reducing the pressure on the forests, in a circular economy and systemic design approach – the main hypothesis of ongoing research at the University of São Paulo. This paper presents the existing problem, the theoretical foundations upon which the study was built, the findings of an international scientific literature review that looked for successful experiences and how the design was involved; and suggests further researches.